THE EFFECTIVENESS OF COOPERATIVE LEARNING TO IMPROVESTUDENTS' ABILITY IN READING : AN EXPERIMENTAL STUDY ON SECOND YEAR STUDENTS OF SMAN 15 BANDUNG - Irma Savitri Sadikin, - (2008)
This research paper entitled "The effectiveness of Cooperative Learning to Improve Students' ability in Reading: An Experimental Study on the Second Year Students of English of SMAN 15 Bandung" aimed to investigate whether or not cooperative learning is effective in improving students' reading comprehension and to discover students' responses toward cooperative learning. The research involved two classes of second grade students SMAN 15 Bandung, which were chosen based on purposive sampling. One class was chosen as the experimental group and another one as the control group. Moreover, the research used experimental pre-test post-test design, and both of the tests were given to experimental and control groups. The results of the study show that the achievement of experimental group is higher than that of the control group. The mean of the experimental group was 7.8 and the mean of control group was 7.3. It means that there is a significant difference in the achievement between the group treated with cooperative learning technique and the group treated with a conventional reading technique. This study has indicated that cooperative learning is effective in increasing reading comprehension. However, this technique also has some weaknesses. It is expected that the study with cooperative learning will be beneficial for the development of teaching reading comprehension skills and give valuable contribution to the process of teaching and learning.